Implementasi Kebijakan Distribusi BBM dan Fenomena Panic Buying di Kota Pontianak dalam Perspektif Mazmanian dan Sabatier - Dita Purnama; Adila Puspa Hestiantini; Utami Nur (Indonesian Democracy Research Center, 2026)
Fuel distribution constitutes a strategic public policy domain with direct implications for social and economic stability, particularly in urban contexts. This study examines the implementation of fuel distribution policy in Pontianak City through the analytical framework of Daniel A. Mazmanian and Paul A. Sabatier, with particular attention to the emergence of panic buying despite the absence of structural shortages. The research adopts a qualitative approach based on a directed literature review and secondary data analysis, drawing on government reports, academic sources, and media coverage. The findings indicate that, from a structural and technical standpoint, fuel supply in Pontianak remains stable and sufficient to meet public demand. Patterns of consumption and distribution suggest that the policy possesses adequate capacity to manage fluctuations in demand. However, empirical evidence reveals persistent long queues and panic buying behavior, pointing to a disjuncture between objective supply conditions and collective public perception. Within the Mazmanian and Sabatier framework, this study finds that neither the tractability of the problem nor the formal capacity of the policy design constitutes the primary constraint on implementation. Instead, non-statutory variables—particularly public perception, information dynamics, and levels of trust—play a decisive role in shaping policy outcomes. Panic buying is thus understood not as a response to material scarcity, but as a socially constructed reaction to perceived uncertainty. This study argues that policy implementation must be understood as a socio-political process in which meaning-making, perception, and trust are central. Consequently, the effectiveness of fuel distribution policy depends not only on material capacity, but also on the state's ability to manage public communication and sustain legitimacy in the eyes of society.